Topology control in wireless sensor networks : with a companion simulation tool for teaching and research - Labrador, Miguel A. (Springer, 2017)
Topology Control in Wireless Sensor Networks addresses the need for a text that combines the background material needed to understand wireless sensor networks with in-depth material about topology control, which is a very important topic related to this technology; and a companion simulation tool of great value for instructors and researchers. Topology Control in Wireless Sensor Networks is a self-contained text for practitioners, engineers, students, professors, and researchers. The first six chapters contain general information about wireless sensor networks and its applications as well as a thorough but concrete description of the most important issues, design guidelines, and available protocols and algorithms utilized at the Physical, MAC, Network, and Transport Layers of the communication protocol stack. In addition, this first part of the book introduces the reader to the concept of topology control, which is expanded to include, for the first time, topology construction and topology maintenance techniques. Parts II and III are devoted to the description and evaluation of topology construction and topology maintenance techniques, providing detailed descriptions of the most important techniques and their effectiveness in their goal to enhance the overall lifetime of wireless sensor networks. Finally, the appendix includes a description of Atarraya, an event-driven simulation tool, designed for teaching and researching topology control algorithms for wireless sensor networks.